From A Nation of Quarter-Humans to that of A Proud People: Technology Transfer and Nationalism in Indonesia (1951-1998) - Suryana, Asep (UI Scholars Hub, 2024)
A series of technology transfer programs took place after Indonesia became fully independent, from 1951 until the fall of the New Order (1998). This article unpacks the ways the authoritarian New Order government utilize nationalist discourses, reproduced in the postcolonial context. These programs were framed as an antithesis to the negative psycho-social aspects of Dutch colonialism as a mean of postcolonial national integration, and as a strategy to make Indonesia’s position more equal to the more developed countries. At the same time, the technology transfer programs relied heavily on the high capacity of the authoritarian state. This study asserts that New Order demonstrates a case of a high capacity authoritarian state that utilized the success of the technology transfer programs, along with nationalist discourses, to legitimize its power. This article expands on the arguments of the previous studies that focus on the strong capacity of the state in promoting the technology transfer. The previous studies tend to neglect the post-colonial context (including the reproduction of the discourses of nationalism) in technology transfer program.